2007
DOI: 10.1016/j.asr.2007.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray burst afterglows

Abstract: Extended, fading emissions in multi-wavelength are observed following Gamma-ray bursts (GRBs). Recent broad-band observational campaigns led by the Swift Observatory reveal rich features of these GRB afterglows. Here we review the latest observational progress and discuss the theoretical implications for understanding the central engine, composition, and geometric configuration of GRB jets, as well as their interactions with the ambient medium.Comment: References added, accepted for publication in Advances in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 185 publications
(285 reference statements)
1
27
0
Order By: Relevance
“…is used (e.g., Sari et al 1999;Zhang 2007). Here, t is the time since burst, α is the temporal index, and β is the spectral index.…”
Section: Fireball Modelmentioning
confidence: 99%
“…is used (e.g., Sari et al 1999;Zhang 2007). Here, t is the time since burst, α is the temporal index, and β is the spectral index.…”
Section: Fireball Modelmentioning
confidence: 99%
“…However, 10 of the 42 GRBs show shallower decay indices and we could not find a reasonable interpretation from the afterglow, neither in uniform ISM nor in wind medium. In addition, we also found that some of the optical shallow decay 1 The single power-law function is F(ν,t) ∝ t −α , where α is a single power-law index and the broken power-law function:…”
Section: Analysis and Resultsmentioning
confidence: 94%
“…steep decays, flares, and shallow decays) were found in many X-ray lightcurves. Those properties, thought to be connected to an active central engine, could be characterized by prompt emission from GRBs or a mixture of different emission components contributing to the observed X-ray emission [1]. In addition, the comparison of X-ray and optical light curves have clearly shown that the evolutions for the two wavelengths are generally different [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of any knee in a decay series can be accounted for by recognizing that some isotope decay chains can have radioactive progeny with higher specific gamma activity than a parent nuclide. Other models have been proposed which tend to adhere to similar power law decay approximations (Zhang 2007). Even with all this, there are additional bumps and wiggles (Maienschein et al 1958) in these fission decay responses due to co-irradiated materials which can depend on interstitial materials (e.g., moderators and poisons), shielding and reflectors.…”
Section: Grb Time Evolutionmentioning
confidence: 99%